2007
DOI: 10.1086/508266
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Judicial Expedience on Attorney Fees in Class Actions

Abstract: Judges facing exogenous constraints on their pecuniary income have an incentive to reduce their workload to increase their private welfare. In the face of an increase in caseload, this incentive will induce judges to attempt to terminate some cases more rapidly. In class action cases, failing to grant an attorney fee request will delay termination. This conflict is likely to lead judges to authorize higher fees as court congestion increases. Using two data sets of class action settlements, we show that attorne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…As for output factors, our regressions feature positive correlation between remedy value and fee and compensation amounts, and a negative correlation between remedy value and fee and compensation percentages. These findings are similar to those found in federal class action settlements in the U.S. (Fitzpatrick 2010, Helland and Klick 2007, Eisenberg and Miller 2004. In other words, the amounts of attorney fees and class representative's compensation rise as the remedy to the class increases, whereas their percentages decline.…”
Section: Attorney Fees and Class Representative Compensationsupporting
confidence: 82%
“…As for output factors, our regressions feature positive correlation between remedy value and fee and compensation amounts, and a negative correlation between remedy value and fee and compensation percentages. These findings are similar to those found in federal class action settlements in the U.S. (Fitzpatrick 2010, Helland and Klick 2007, Eisenberg and Miller 2004. In other words, the amounts of attorney fees and class representative's compensation rise as the remedy to the class increases, whereas their percentages decline.…”
Section: Attorney Fees and Class Representative Compensationsupporting
confidence: 82%
“…rendering higher fees to attorneys as caseload rises (Eisenberg et al 2014). Similarly, Helland & Klick (2007) found that when facing an increase in caseload, judges authorize higher attorney fees in class action suits, presumably in order to induce the rapid termination of these cases. Finally, time pressure can also reinforce a tendency to give greater deference to primary decision-makers, thus decreasing the likelihood of winning administrative cases and civil or criminal appeals (Guthrie & George 2004, Huang 2011, Giles et al 2015).…”
Section: B Micro Judicial-behavior Level: What Do Judges Maximize?mentioning
confidence: 99%
“…They find that judges who face crowded dockets are more likely to approve higher attorney's fees, all other case characteristics held constant. See Helland and Klick (2007). 15 There have not been, to my knowledge, empirical studies of these lead-counsel auctions to reveal whether they are, in fact, superior compensation methods.…”
Section: Adverse Selection and Opt-outsmentioning
confidence: 99%